Analysis of the Effect of CR, NPM, ROA, ROE and GPM on Stock Returns of Go Public Banking Companies Listed on the IDX - Hurriyaturrohman, Hurriyaturrohman; Rizki, Sinta Dewi; Ningrum, N.ARumiasih. (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2024)
This research aims to determine the influence of Current Ratio, Net Profit Margin, Return on Assets, Return on Equity and Gross Profit Margin, whether these variables influence stock returns in the banking sector for the period before (2018-2019), the period after (2020-2021) and over the last five years (2018-2022) Companies listed on the Indonesia Stock Exchange in 2018-2022 are the subject of this research. This research also used purposive sampling techniques to collect 11 companies from 47 companies in the banking industry. This research uses secondary data, which is analyzed using multiple linear regression analysis methods, T tests, and F tests for sample companies. banking will go public in 2022. The research results show that the Current Ratio, Net Profit Margin, Return on Assets, Return on Equity and Gross Profit Margin in the period before had a negative effect on stock returns, but after the Covid-19 pandemic and during the last four years the variables had a positive effect on stock returns